(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2025)
Leon Petrażycki (1867–1931) is one of the most original figures in the history of sociology of law, philosophy of law, and generally in the history of broadly understood humanities and social sciences. In academic circles, L. Petrażycki is mainly known as the founder of the psychological theory of law, but it is hardly ever emphasised that he was a scientist who recognised the important role of religion in social and moral processes. Unlike many of his contemporaries, he did not reject religion as a relic, but recognised it as a real force for education and the formation of social consciousness. At the same time, he emphasised that the function and significance of religion in the historical process (progress) would become exhausted and thus inevitably eroded.